Nitric oxide treatment for fulminant pulmonary hypertension. Issue 4 (October 1993) - Allman, K G; Young, J D; Stevens, J E; Archer, L N
Abstract : A 3 year old child with known pulmonary haemosiderosis suffered acute circulatory collapse secondary to raised pulmonary vascular resistance. Nitric oxide inhalation produced a profound improvement in circulatory parameters and gaseous exchange. Nitric oxide may have a therapeutic role in acute pulmonary hypertensive crisis.